Research on the spatial and temporal evolution and coupling effects of carbon emissions and net carbon sinks on arable land in China - Xiaofan Wang; Qinxuan Wang; Lili Yao (Frontiers in Sustainable Food Systems)
The Chinese government’s “30–60” carbon reduction target demonstrates its NDCs (Nationally Determined Contributions) regarding global climate issues. At the same time, the global food security situation is at risk of a new wave of uncertainty; balancing ecological and economic benefits has become a realistic problem that China’s arable land utilization needs to consider. This study examines the carbon emissions and net carbon sinks associated with cropland utilization across 31 provinces, cities, and districts in China over the period from 1991 to 2022. It provides a comprehensive accounting of these metrics and elucidates their spatiotemporal evolution characteristics. Furthermore, by employing an enhanced Tapio coupling index, the research delves into the intricate relationship between the net carbon sink of cropland utilization and grain yield, offering valuable insights into their interdependencies. The study found that: (1) China’s carbon emissions from arable land use on a downward trend after 2016; Between 1991 and 2022, there has been a notable decline in the number of Tier 1 and Tier 2 carbon-emitting provinces and municipalities in China. Specifically, the count has reduced from 21 provinces and municipalities, which included Inner Mongolia, Ningxia, Heilongjiang, and Jilin in 1991, to 13 provinces and municipalities by 2022. (2) China’s net carbon sinks from arable land use are now in a high growth phase; the net carbon sinks of each province have increased significantly compared with the previous one, and the high average annual net carbon sinks are spatially dispersed. (3) Most of the provinces in the main grain-producing regions are located in high-sink and high-yield areas; the net carbon sink has been coupled with grain production since 2004, and the coupling status of each province is more diversified. Based on the above findings, targeted optimization strategies are proposed from the perspective of low-carbon and high-yield use of arable land, and strategies for high-quality development of green agriculture are actively explored and implemented.